We are given the function
![f(x)=x+6](https://img.qammunity.org/2023/formulas/mathematics/college/5xo4ebbh2ma6ew7bk2qsdreuz23f5641qm.png)
We are to reflect the function f(x) over the x axis
The rule to reflect a function over x axis is given as
![(x,y)\Rightarrow(x,-y)](https://img.qammunity.org/2023/formulas/mathematics/college/momd9tfmosfazmpp5qbkpvva58nofodiqe.png)
Let f(x) = y
Then
![y=x+6](https://img.qammunity.org/2023/formulas/mathematics/high-school/r98z9ljiaai68qqhgmhswqi3o21ge6xso5.png)
Hence for the reflection
x = x, y = -y
Hence, the reflection is
![-y=x+6](https://img.qammunity.org/2023/formulas/mathematics/college/p80jrrx5ie17wollh8j3wcxg18e4iaqu9j.png)
Simplifying this we get
![y=-x-6](https://img.qammunity.org/2023/formulas/mathematics/college/8vm2cg6lq4y9osgdjcgoudnm2ge0ue9t2s.png)
Thereforem the reflection g(x) is
![g(x)=-x-6](https://img.qammunity.org/2023/formulas/mathematics/college/jbeeomri71hy3tz0d3h21ncdqzgpmkbb6b.png)